Plant architecture and prey distribution influence foraging behavior of the predatory mite Phytoseiulus persimilis (Acari: Phytoseiidae) - Gontijo, Lessando M.; Nechols, James R.; Margolies, David C.; Cloyd, Raymond A. (My University, 2012)
The arrangement, number, and size of plant parts may influence predator foraging behavior, either directly, by altering the rate or pattern of predator movement, or, indirectly, by affecting the distribution and abundance of prey. We report on the effects of both plant architecture and prey distribution on foraging by the predatory mite, Phytoseiulus persimilis Athias-Henriot (Acari: Phytoseiidae), on cucumber (Cucumis sativus L.). Plants differed in leaf number (2- or 6-leafed), and there were associated differences in leaf size, plant height, and relative proportions of plant parts; but all had the same total surface area. The prey, the twospotted spider mite Tetranychus urticae Koch (Acari: Tetranychidae), were distributed either on the basal leaf or on all leaves. The effect of plant architecture on predator foraging behavior varied depending on prey distribution. The dimensions of individual plant parts affected time allocated to moving and feeding, but they did not appear to influence the frequency with which predators moved among different plant parts. Overall, P. persimilis moved less, and fed upon prey longer, on 6-leafed plants with prey on all leaves than on plants representing other treatment combinations. Our findings suggest that both plant architecture and pattern of prey distribution should be considered, along with other factors such as herbivore-induced plant volatiles, in augmentative biological control programs.
Citation: Gontijo, L. M., Nechols, J. R., Margolies, D. C., & Cloyd, R. A. (2012). Plant architecture and prey distribution influence foraging behavior of the predatory mite Phytoseiulus persimilis (Acari: Phytoseiidae). Retrieved from http://krex.ksu.edu
Keywords: Plant architecture; Prey distribution; Predator foraging behavior; Tetranychus urticae; Phytoseiulus persimilis; Biological control